Pengaruh Perbedaan Jenis Dan Konsentrasi Larutan Alkali Terhadap Kekuatan Gel Dan Viskositas Karaginan Kappaphycus alvarezii, Doty - Romenda, Ardiawan Pandu; Pramesti, Rini; Susanto, Antonius Budi (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Carrageenan is a seaweed sap extracted by water or alkali solution from certain species Rhodophyceae class (red algae). The raw materials are used in various food and non-food industrial. The process of making SRC performed by using alkali type strong base KOH and NaOH with 4%, 6% and 8% concentration. Analysis is measured gel strength and viscosity of each type and concentration. KOH alkali treatment values are 4, 6 and 8% of the gel strength is 192.00 ± 1.12 g/m²; 630.71 ± 10.32 g/m²; 385.85 ± 3.70 g/m². NaOH 4, 6 and 8% of the gel strength is 184,63 ± 4,48 g/m²; 321,26 ± 46,12 g/m²; 452,24 ± 125,45 g/m². KOH alkali treatment values are 4, 6 and 8% of the viscosity was 22.24 ± 0.20 cPs; 24.61 ± 0.3 cPs; 20.00 ± 0.15 cPs; NaOH 4, 6 and 8% of the viscosity is cPs 22.58 ± 0.26; 25.07 ± 0.17 cPs; 25.07 ± 0.17 cPs. Based on the results of the study the highest gel strength is at 6% KOH and highest viscosity at 6% NaOH.